Process Systems Engineering Evaluation of Prospective Working Fluids for Organic Rankine Cycles Facilitated by Biogas Combustion Flue Gases - Qyyum, Muhammad Abdul; Naquash, Ahmad; Ali, Wahid; Haider, Junaid; Noon, Adnan Aslam; Rehan, Mohammad; Nizami, Abdul-Sattar; Yasin, Muhammad; Lee, Moonyong (Frontiers in Energy Research, 2021)
The organic Rankine cycle (ORC) has recently emerged as a practical approach for generating electricity from low-to-high-temperature waste industrial streams. Several ORC-based waste heat utilization plants are already operational; however, improving plant cost-effectiveness and competitiveness is challenging. The use of thermally efficient and cost-competitive working fluids (WFs) improves the overall efficiency and economics of ORC systems. This study evaluates ORC systems, facilitated by biogas combustion flue gases, using n-butanol, i-butanol, and methylcyclohexane, as WFs technically and economically, from a process system engineering perspective. Furthermore, the performance of the aforementioned WFs is compared with that of toluene, a well-known WF, and it is concluded that i-butanol and n-butanol are the most competitive alternatives in terms of work output, exergy efficiency, thermal efficiency, total annual cost, and annual profit. Moreover, the i-butanol and n-butanol-based ORC systems yielded 24.4 and 23.4% more power, respectively, than the toluene-based ORC system; in addition, they exhibited competitive thermal (18.4 and 18.3%, respectively) and exergy efficiencies (38 and 37.7%, respectively). Moreover, economically, i-butanol and n-butanol showed the potential of generating 48.7 and 46% more profit than that of toluene. Therefore, this study concludes that i-butanol and n-butanol are promising WFs for high-temperature ORC systems, and their technical and economic performance compares with that of toluene. The findings of this study will lead to energy efficient ORC systems for generating power.